Concurrent axon and myelin destruction differentiates X‐linked adrenoleukodystrophy from multiple sclerosis. Issue 10 (17th June 2021) - Bergner, Caroline G.; Genc, Nafiye; Hametner, Simon; Franz, Jonas; van der Meer, Franziska; Mitkovski, Miso; Weber, Martin S.; Stoltenburg‐Didinger, Gisela; Kühl, Jörn‐Sven; Köhler, Wolfgang; Brück, Wolfgang; Gärtner, Jutta; et al.
Abstract: Cerebral disease manifestation occurs in about two thirds of males with X‐linked adrenoleukodystrophy (CALD) and is fatally progressive if left untreated. Early histopathologic studies categorized CALD as an inflammatory demyelinating disease, which led to repeated comparisons to multiple sclerosis (MS). The aim of this study was to revisit the relationship between axonal damage and myelin loss in CALD. We applied novel immunohistochemical tools to investigate axonal damage, myelin loss and myelin repair in autopsy brain tissue of eight CALD and 25 MS patients. We found extensive and severe acute axonal damage in CALD already in prelesional areas defined by microglia loss and relative myelin preservation. In contrast to MS, we did not observe selective phagocytosis of myelin, but a concomitant decay of the entire axon‐myelin unit in all CALD lesion stages. Using a novel marker protein for actively remyelinating oligodendrocytes, breast carcinoma‐amplified sequence (BCAS) 1, we show that repair pathways are activated in oligodendrocytes in CALD. Regenerating cells, however, were affected by the ongoing disease process. We provide evidence that—in contrast to MS—selective myelin phagocytosis is not characteristic of CALD. On the contrary, our data indicate that acute axonal injury and permanent axonal loss are thus far underestimated features of the disease that must come into focus in our search for biomarkers and novel therapeutic approaches. MAIN POINTS: This study characterizes CALD as an axonopathic disease. Microglia cell death in CALD early lesion formation is associated with severe axonal damage. Microglia homeostasis may be linked to axonal energy metabolism.